Evaluation of anti-inflammatory activity of hydroalcoholic extract of Ananas cosmosus fruit peel by HRBC membrane stabilization - Y. Niharika (International Journal of Pharmacy and Analytical Research, 2022)
The aim of the study is to determine the in-vitro anti-inflammatory activity of the hydroalcoholic extract of Ananas Cosmosus fruit peel by HRBC membrane stabilization. Hypotonicity induced human red blood cell (HRBC) membrane stabilization method was performed to check the anti -inflammatory activity of Ananas Cosmosus. The extract was compared with a standard synthetic drug Diclofenac to check the anti -inflammatory activity. Haemolysis and protective activity of both the drugs were checked and analyzed. Results showed significant anti-inflammatory activity but was less compared to the standard drug. Inflammation has to be treated prior to the disease treatment since decreasing pain is first step in a treatment procedure. This is wher e the anti-inflammatory drugs act and eventually decrease the inflammation. Diclofenac being a synthetic drug can lead to a lot of side effects. Ananas Cosmosus being a natural drug has fewer side effects comparatively and can be used in combination with o ther drugs in future in giving and efficient anti -inflammatory drug.